Pengaruh Sikap Keuangan, Pengalaman Keuangan dan Kepribadian terhadap Perilaku Pengelolaan Keuangan UMK di Kecamatan Lubuk Dalam Kabupaten Siak - Cristamar, Yemima Ayu; Ruzikna, Ruzikna (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of financial attitudes, financial experience and personality on the financial management behavior of MSEs in Lubuk Dalam District, Siak Regency. The method used in this research is quantitative descriptive analysis with the SmartPLS 4 program. The population in this research is all micro and small business actors in Lubuk sub-district, totaling 1648 MSE units, with a total sample of 94 MSE units. The data collection technique is through distributing questionnaires, while the variable measurement technique uses a Likert scale. Data analysis includes convergent validity test, discriminant validity test, reliability test, model fit test, coefficient of determination test, path coefficient test and hypothesis testing. The results of the analysis show that in general the financial attitudes, financial experience, personality and financial management behavior of MSEs in Lubuk District are very good. In addition, the results of this research show that (1) financial attitudes have a positive and significant effect on financial management behavior of MSEs in Lubuk Dalam District, (2) financial experience has a positive and significant effect on financial management behavior of MSEs in Lubuk Dalam District and (3) personality has a positive and significant effect on the financial management behavior of MSEs in Lubuk Dalam District. Keywords: Financial Attitudes, Financial Experience and Personality, Financial Management Behavior.